ASSOCIATION OF CIGARETTE SMOKING AND RISK OF URINARY BLADDER CANCER : A SYSTEMATIC REVIEW - Kusumo, Bayu; Fadiyah Mahrunnisa, Inannami (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: It has been proposed that smoking cigarettes increases the likelihood of urinary bladder cancer (UBCa). But not everyone who smokes heavily gets these illnesses, and first-degree relatives' higher cancer risk points to a significant hereditary component.Aims : This systematic review is to review the association between cigarette smoking and its risk of urinary bladder cancer in men and women.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 729 articles, whereas the results of our search on SAGEPUB brought up 1495 articles, our search on SCIENCE DIRECT brought up 11284 articles. The results of the search conducted for the last year of 2014 yielded a total 177 articles for PubMed, 442 articles for SAGEPUB and 3775 articles for SCIENCE DIRECT. In the end, we compiled a total of  8 papers, 5 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included eight research that met the criteria.Conclusion: In summary, tobacco smoking was a strong risk factor for bladder cancer for both men and women.